A NEW VISION FOR URBAN TRANSPORT IN MISURATA - Abdallah .N. kamba (European Scientific Journal, ESJ, 2014)
The problem of traffic and transportation has led to frustration, lossof time, fuel and waste of effort in organizing and controlling traffic. Thiswasted time is as a result of slow movement with increasing delays and hasled to difficulties with respect to punctuality and interviews. Also, it hasextended the energy and effort and increase in the proportion of air pollutionand deterioration of behavior, as well. The problem of congestion duringpeak hours is due to the high population density and increased transportationand the growing demand for use in its various forms. In addition, this can beseen in light of the survival networks of roads and bridges intact without anydevelopment or change to accommodate changes as a result of this increase.The researcher in this study examined the factors and variables affecting theurban transport such as land uses in the urban area, urban development andurban sprawl horizontal and increase in the density of urban areas, as well asthe study of the elements of assessing the efficiency of urban transportsystem and the basic principles of urban transport in Misurata.